Electric power generation, transmission, and distribution - Grigsby, Leonard L. (Electric power engineering series., 2012)
Featuring contributions from worldwide leaders in the field, the carefully crafted Electric Power Generation, Transmission, and Distribution, Third Edition (part of the five-volume set, The Electric Power Engineering Handbook) provides convenient access to detailed information on a diverse array of power engineering topics. Updates to nearly every chapter keep this book at the forefront of developments in modern power systems, reflecting international standards, practices, and technologies. Topics covered include: * Electric Power Generation: Nonconventional Methods * Electric Power Generation.